Physiochemical evaluation and tribological properties of eco-friendly biodegradable novel biolubricant from banana peel wastes - A. Hamid, Husna (2017)
Banana peel,which known as a waste product was shown to have a potential sources of plant/vegetable oils due to slippery effect from the existence of hemicellulose of follicular gels contained in its epicarps.From the literature surveys,it was noted that,limited scientific studies are available on banana peels and has not been given great attention by the researchers.The present study is to extract the oil form banana peel waste of Musa Aliminata Balbisiana (MBS),characterize the physical,physiochemical properties,chemical compositional and functional group analysis,fatty acids profile and wettability analysis of the oil,investigate the tribological behavioural of MBS Oil at different temperatures and loads,investigate the effect of biodegradable additive of Ethyl Cellulose (EC) and Ethylene Vinyl Acetate (EVA) on tribological performance of MBS oil,analyse the predominant wear mechanism of MBS Oil under wet sliding condition and formulate a mathematical equation for friction and wear of MBS Oil with the presence of EC and EVA using ANOV A Analysis. The peel waste of MBS contained 86.57% of moisture and 0.57% of volatile content.Surface morphology analysis revealed that the existence of follicular gel in the epicarp of peel waste of MBS that was functioned to trapped the oil constituents thus create the slippery effect.A pale brownish of novel bio-oil from banana peel waste of MBS was extracted using soxh/et extraction method.In this methods,11-hexane was used as solvent of extractor at the optimum condition at the temperature of 68 °C for 7 hour.The pale brownish oil exhibit a density at 40 °C of 0.8502 kg/m3 and specific gravity of 0.8536. Physiochemical analysis revealed that,the MBS oil exhibited a refractive index (Rl) of 1.74 and 3.29 eSt of viscosity at 40 °C.Besides,MBS oil contained 2.64 of Free Fatty Acids (FF As),0. 77 g of l:z/ 100 g of oil iodine Values (IV),and 7.46 mg KOH/g Saponification Values (SV), Total Acid Number (TAN) and Total Base Number (TBN) of 0.52 mg KOH/g and 0.77 mg KOH/g respectively.FT-IR analysis showed that,the oil contained an ester of carbonyl functional group,C=O ( 1733.06 cm·1),C-H of cis-di-substituted olefins (1644.42 cm-1) ,=C-H aliphatic groups (1453.39 cm-1),CO ester group (1 244.10 cm·1, 11 73.29 cm·1,1094.79 cm·1,1039.58 cm·1 and 982.34 cm-1) and -CH2 (72 1.11 cm·1) .MBS oil exhibited a wettability analysis at the contact angle values of 157.55°.Fatty acid analysis revealed that MBS Oil composed of 46% of saturated fatty acids (SF As),46% of monounsaturated fatty acids (MUF As) and 4% of polyunsaturated fatty acids (PUF As).Fatty acids compositional analysis showed that,MBS oils was dominated by Butyric Acid (C4:0), Caproic Acid (C6:0),Myristic Acid (C 14:I), Ginkgolic acid (C 15: I),Gondoic Acid (C20: I ),Methyl Nerranoic Acid (C24: I),Gamma-Linolenic Acid (C 18:3N6) and cis-8, 11,14-Eicosatrienoic Acid (C20:3N6).MBS oil showed a lower coefficient of friction,COF values at the load of 80N at 27 °C,40 oc and 100 oc with the ranged of 0.05 to 0.13.Wear Scar Diameter,WSD analysis ranged from 251 J.lm to 1233 J.lm and Wear rate,Ws analysis shows that,it in the ranged from 0.0 16 x 10·15 to 4.0396 x 10"15 mm3/Nmm. The presences of EC and EVA at difference concentration were lead to reduction in COF values for MBS oil due to the synergism effects between EC and EV with the existences of fatty acid compounds in MBS Oil.The predominant wear mechanisms in the tribological study of MBS oil with the presence of EC and EVA were adhesive and abrasive wear which proved by the SEM micrograph and SEM EDX mapping.A mathematical equation for friction and wear were formulated.